Routing Algorithm Based on Communication Quality in Wireless Senor Network - Song, Feng an; Hong, Wang; Xiao-yu, Ge (International Journal of Online and Biomedical Engineering (iJOE), 2015)
The graph routing is a kind of routing mechanism proposed in the wireless senor network. At present, there is less research on the graph routing algorithm. In this paper, a routing algorithm of wireless senor network based on Received Signal Strength Indication (RSSI) and path stability is presented. The hierarchical algorithm based on RSSI of the communication link was adopted and guaranteed the least hop and communication reliability. The paper takes advantage of the hierarchical algorithm based on RSSI to ensure minimum number of hops and communication availability. A communication link quality mechanism based on path stability and RSSI that is used for communication nodes among layers is proposed. The routing among layers is selected based on the communication quality mechanism. The source routing is realized and used to the unicast downstream data transmission in Wireless senor network. The paper realized the source routing based on path stability.